An eight-weeks resistance training programme with elastic band increases some performance-related parameters in pubertal male volleyball players - Hammami, R.; Gene-Morales, J.; Abed, F.; Amin Selmi, M.; Moran, J.; Colado, J. C.; Hem Rebai, H. (Biology of Sport, 2022)
The main aim was to evaluate the changes in dynamic, reactive, and power strength, and balance (as volleyball performance-related parameters) in pubertal volleyball players when a part of their normal in season training regimen was replaced by an elastic band training (EBT). 27 male elite volleyball players were randomly allocated to intervention (N = 14; 14.86 ± 0.52 years) or control group (N = 13; 14.74 ± 0.36 years). The intervention consisted of an 8-week EBT program focused on the training of the lower limb, with different volumes and intensities. Countermovement jump (CMJ) and standing long jump (SLJ) were used to assess the power strength, squat one repetition-maximum, and reactive strength index to assess dynamic and reactive strength, respectively. Also, the balance was assessed through different parameters of the foot centre of pressure (CoP) displacements obtained with a force platform. An ANOVA of repeated measurements and post-hoc tests evaluated differences between groups and between baseline and post-intervention. Dynamic and power (CMJ and SLJ) strength, and anteroposterior displacement of the CoP were improved after the intervention. The control group only improved the dynamic strength. No statistically significant difference (p > 0.05) were found in the rest of the variables. EBT improves jump performance and other volleyball performance-related parameters in adolescent male athletes and should be considered to complement regular volleyball in-season training.